#### My Profile

1. Inform you about time table of exam.

2. Inform you about new question papers.

3. New video tutorials information.

#### Question

Prove the following identities:

`(i) (sinθ + cosecθ)^2 + (cosθ + secθ)^2 = 7 + tan^2 θ + cot^2 θ`

`(ii) (sinθ + secθ)^2 + (cosθ + cosecθ)^2 = (1 + secθ cosecθ)^2`

`(iii) sec^4 θ– sec^2 θ = tan^4 θ + tan^2 θ`

#### Solution

#### Similar questions VIEW ALL

Prove the following identities, where the angles involved are acute angles for which the expressions are defined

`(cosec θ – cot θ)^2 = (1-cos theta)/(1 + cos theta)`

Prove the following trigonometric identities:

(i) (1 – sin^{2}θ) sec^{2}θ = 1

(ii) cos^{2}θ (1 + tan^{2}θ) = 1

Prove the following identities:

`( i)sin^{2}A/cos^{2}A+\cos^{2}A/sin^{2}A=\frac{1}{sin^{2}Acos^{2}A)-2`

`(ii)\frac{cosA}{1tanA}+\sin^{2}A/(sinAcosA)=\sin A\text{}+\cos A`

`( iii)((1+sin\theta )^{2}+(1sin\theta)^{2})/cos^{2}\theta =2( \frac{1+sin^{2}\theta}{1-sin^{2}\theta } )`

Prove the following identities, where the angles involved are acute angles for which the expressions are defined.

`sqrt((1+sinA)/(1-sinA)) = secA + tanA`

Choose the correct option. Justify your choice.

(secA + tanA) (1 − sinA) =

A) secA

(B) sinA

(C) cosecA

(D) cosA